The Culture of Swapping Children’s Clothes Between Mothers in Saudi Arabia and its Relationship to Sustainability in Consumer Behavior - Qasti, Aroub Abdullah; Al-Dabbagh, Maha Abdullah (Journal of Humanities & Social Sciences, 2023)
This study explores the emerging trend of swapping children’s clothes as a sustainable practice and analyzes mothers’ acceptance of this phenomenon. Using a descriptive-analytical approach, the research surveyed mothers’ attitudes towards this practice through a questionnaire. The research sample for this study consisted of 138 respondents who were mothers from various regions of the Kingdom of Saudi Arabia. The primary research tool used in this study was a questionnaire. This questionnaire aimed to gauge the extent to which mothers are receptive to the idea of swapping children’s clothes. The study found that a large majority (88.3%) of the mothers surveyed know the practice of swapping children’s clothes, indicating that this concept is widely known among the participants. Moreover, most mothers surveyed (83%) have engaged in swapping children’s clothes with family or friends. This high level of participation suggests that this form of swap is a common practice. Most mothers who have engaged in the exchange (76%) have done it more than once. This suggests that once mothers begin participating in this practice, they will likely continue, indicating a positive experience or perceived benefits from the exchange. More than half of the mothers (60.1%) do not feel embarrassed to propose such an exchange, which is a positive sign for this practice’s continuation and potential growth. However, 40% of mothers feel or may feel embarrassed, indicating that social and emotional barriers could hinder the wider adoption of this practice. The study underscores the need to boost awareness about the environmental benefits of such exchanges, given the typically brief usage span of children’s clothes due to their rapid growth. It also proposes innovative strategies to enhance clothing exchange gatherings and advocates for instilling the principles of swap and giving in the younger generation to reinforce the concept of sustainability in clothing.